GARCÍA HURTADO, Manuel-Reyes y REY CASTELAO, Ofelia (eds.), Fronteras de agua. Las ciudades portuarias y su universo cultural (siglos XIVXXI), Santiago de Compostela: Universidade de Santiago de Compostela, 2016, 570 p. ISBN: 978-84-16533-87-9. (Estudios Humanísticos. Historia, 2017)
Reseña